(untitled) (The East and Central African Journal of Pharmaceutical Sciences, 2018)
Insulin storage methods and the techniques of its administration impact on blood sugar control. A hospital based cross-sectional study was conducted to assess the effects of insulin administration techniques and storage on the long term control of blood glucose among 73 freely consenting adult diabetic outpatients at Kenyatta National Hospital. Participants were selected through convenient sampling and interviewed using a pre-designed questionnaire. Long term glycaemia control was assessed by measuring the blood levels of glycated haemoglobin. Ethical approval was granted by the institutional review board and participants’ confidentiality was maintained throughout the study. Data analysis was done using STATA version 10 software; with statistical significance set at 95% confidence limit. Logistic regression was used to determine associations between glycated haemoglobin levels versus insulin storage methods and the administration techniques. Correct performance of the critical injection techniques (p=0.0001), insulin storage by refrigeration (p=0.041) and during travel (p=0.019) were associated with good long term glycaemic control. Patients need to be regularly encouraged on good insulin injection techniques and storage methods in order to improve long term glycaemic control.